Effects of anatomical variation of muscle on composition and oxidation susceptibility of Atlantic mackerel (Scomber scombrus). (July 2021) - Sveinsdóttir, Hildur Inga; Sverrisdóttir, Sandra Björk; Karlsdóttir, Magnea G.; Rustad, Turid; Arason, Sigurjón; Gudjónsdóttir, María
Abstract: Atlantic mackerel ( Scomber scombrus ) is a fatty fish with high ratio of dark muscle. The subcutaneous muscle on the dorsal and ventral side of the fillet is prone to yellow discolouration, attributed to lipid oxidation. The question is if this is solely due to the position of the muscle under the skin or if this muscle is more susceptible to oxidation than other dark muscle. The aim of the study was to evaluate if anatomical variation in the muscle of Atlantic mackerel could affect the oxidation susceptibility and/or its processability. Water and lipid content, fatty acids composition, colour and lipid oxidation (assessed by heme-iron content) and hydrolysis (assessed by free fatty acid ratios) susceptibility were determined. Heme-iron content of dark muscle differed depending on anatomical position and was higher dorsal and ventral dark muscle than in other dark muscle, indicating higher oxidation susceptibility. Furthermore, the ventral and dorsal light muscle and the medial dark muscle had lower free fatty acid content (0.57–1.15 g FFA/100 g lipids) compared to lateral and ventral dark muscle (3.40–3.62 g FFA/100 g lipids). The results indicate that lateral, ventral and dorsal dark muscle are more susceptible to lipid oxidation and hydrolysis. Highlights: Composition of light and dark muscle from mackerel slightly varied based on anatomical position. Subcutaneous dorsal and ventral dark muscle contains higher heme-iron than other parts of muscle. Subcutaneous dark muscle had more lipid oxidation and hydrolysis susceptibility than light and medial dark muscle. Removing subcutaneous muscle through deep skinning of Atlantic mackerel may increase stability.